CORRIENTES ELÉCTRICAS ALINEADAS CON EL CAMPO GEOMAGNÉTICO EN BAJAS LATITUDES MAGNÉTICAS - Rojas Acuña, Joel (1999)
The existence of electric currents aligned with the magnetic field at low latitudes has been inferred using the methods of Gettemy [1] and Fukushima [2] applied to the magnetic data recorded in Peru during the International Geophysical Year (IGY) and the International Equatorial Electrojet Year (IEEY). The representation of the solar quiet daily magnetic variation, Sq, using magnetic contour maps of the D, H, and Z components of the magnetic field recorded at the Huancayo Magnetic Observatory (OMH) for the two time periods(1957 - 1958 and 1990 - 1991) was designed to visualize the seasonal changes in the daily variation. The maps obtained in this work are similar to the ones obtained by Gettemy [1] for the Magnetic Observatory at Koror (OMK) at the Palao Islands (Pacific Ocean) during IGY. The magnetic contour maps for the components of the magnetic field recorded at the Observatory of Ancon (OMA) for the period of 1990 - 1991are also very similar to the ones from Huancayo and Koror, even in different time periods. Likewise, the magnetic contour maps for 5 other magnetic stations at other equatorial sites (1958) are prepared for the purpose of comparison and interpretation. Two diagrams referred to the patterns of the upper electric current system of the solar quiet magnetic variation, Sq, for 1/2 (Summer + Winter) and 1/2(Summer - Winter) at low magnetic latitudes were prepared using the method of analysis for the ground daily magnetic variations as proposed by Fukushima [2] for middle magnetic latitudes and applied to four magnetic magnetic stations in Japan. The results obtained allow us to infer the aligned electric currents with the geomagnetic field at low latitudes and confirm the seasonal inversion in the daily magnetic variation of the declination at the OMH and in the OMA.